Population pharmacokinetics modelling to predict DDI from zopiclone on clozapine in schizophrenia patients - Han, Huan-Huan; Zhang, Yue; Wang, Jie; Tian, Xue; Li, Ye; He, Su-Mei; Zhang, Cun; Chen, Xiao; Wang, Dong-Dong (Frontiers in Psychiatry, 2025)
IntroductionClozapine, as a core drug for the treatment of schizophrenia, is widely used in the drug treatment of schizophrenia patients. However, when multiple drugs are used in combination, it is not clear whether there are drug-drug interactions (DDI) of clozapine in patients with schizophrenia. This study aims to use population pharmacokinetics (PPK) modelling to predict DDI and individualized therapy of clozapine in schizophrenia patients.MethodsWe collected 81 patients with schizophrenia and included their physiological data, biochemical data, treatment plans and information on combined medication during the clinical treatment process. Next, PPK modelling was used to analyze drugs with potential DDI when clozapine was used in schizophrenia patients, and dosage adjustments were recommended.ResultsFinal analysis revealed that weight and coadministration of zopiclone affected clozapine clearance, and there was DDI with clozapine when zopiclone was used concurrently in schizophrenia patients. Further, for schizophrenia patients without zopiclone, 10 mg/kg/day, 9 mg/kg/day, 8 mg/kg/day and 7 mg/kg/day clozapine were recommended for 40–50 kg, 50–67 kg, 67–88 kg, and 88–120 kg patients, respectively. For schizophrenia patients with zopiclone, 6 mg/kg/day and 5 mg/kg/day clozapine were recommended for 40–70 kg and 70–120 kg patients, respectively. This study was the first to systematically analyze DDI when clozapine was used in schizophrenia patients and found DDI when zopiclone and clozapine were taken concurrently.ConclusionWhen zopiclone was taken concurrently, clozapine dosage need to be reduced. Based on this, schizophrenia patients individualized dosage adjustment was recommended.